The acquisition of a series of phrasal verbs in the course integrated English I at the University of Costa Rica = la adquisición de una serie de verbos frasales en el curso "Inglés integrado I" en la Universidad de Costa Rica - Navas Brenes, César Alberto 1976- (2017)
This article is aimed at observing the acquisition and assessment of a list of forty phrasal verbs in a group of first-year students of the course LM-1001 Integrated English I at the University of Costa Rica. First of all, the author implements a placementtest to determine the students' proficiency level, being Integrated English I the first EFL course of the program. Then, the author administers two instruments to assess the students' knowledge on a series of phrasal verbs before the presentation, practice, and production throughout the second part of the semester. A contextualized sample lesson to practice a selection of phrasal verbs is also included. To finish, the students receive two additional instruments and a final evaluative instrument to observe the level of acquisition of twenty phrasal verbs as a result of explicit instruction.
Este artículo pretende observar la adquisición y evaluación de una lista de cuarenta verbos frasales en un grupo de estudiantes de primer año del curso LM-1001 Inglés Integrado I en la Universidad de Costa Rica. Primero, el autor aplica un examen de ubicación para determinar el nivel de losestudiantes, siendo el primer curso de la Carrera de Inglés. Posteriormente, el autor aplica dos instrumentos para evaluar el conocimiento de una serie de verbos frasales antes de la presentación, práctica, y producción a lo largo de la segunda parte del semestre. Se incluye una lección para practicar una selección de verbos frasales en contexto. Por último, los estudiantes reciben un último instrumento evaluativo para observar el nivel de adquisición de únicamente veinte verbos frasales como resultado de la instrucción explícita.
En Revista Intersedes, vol. 18, no. 38 (marzo 2017)
Descripción basada en el contenido visto el 7 de febrero, 2025